Poverty in Latin America - Leonardo Gasparini; Maria Emma Santos; Leopoldo Tornarolli (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2021)
This chapter discusses the measurement of monetary and multidimensional poverty in Latin America, and documents the main patterns and trends. By providing an updated assessment of the level, changes and characteristics of poverty in the region we expect to contribute to the more ambitious debate on its determinants and policy implications.
Keywords: I3; I32; 330; Armut; Messung; Armutsbekämpfung; Lateinamerika